FORMATION OF WOMEN'S BODY IMAGE IN THE “IMPERFECT” FILM FOR GENERATION Z IN INDONESIAN - Safitri Nur Aeni; Edy Prihantoro; Diana Sari (Journal of Digital Media Communication, 2022)
“Imperfect” is one of the inspirational films for generation Z women in Indonesia today. The film is a medium to provide information and entertainment to the community. Films can provide education, knowledge, and entertainment for the audience so that they can influence the audience to change according to the film's purpose. This study aimed to determine the effect of exposure and information quality of “Imperfect”  films on the body image formation of Indonesian Z-generation women. The research method used is quantitative research methods. The theory used is the theory of Uses and Gratification and the Theory of Social Comparison, which helps support body image formation. The results of the study indicate that there is an effect of exposure to “Imperfect” films and the quality of the film's information on the body image formation of Indonesian generation Z women. People who get information about the “Imperfect” film are interested in watching the film, in getting entertainment as well as information from the “Imperfect” film, especially the generation Z female group. Indonesia.